Von Willebrand factor propeptide in severe coronavirus disease 2019 (COVID‐19): evidence of acute and sustained endothelial cell activation. (16th December 2020) - Ward, Soracha E.; Curley, Gerard F.; Lavin, Michelle; Fogarty, Helen; Karampini, Ellie; McEvoy, Natalie L.; Clarke, Jennifer; Boylan, Maria; Alalqam, Razi; Worrall, Amy P.; Kelly, Claire; de Barra, Eoghan; et al.
Summary: Endothelial cell (EC) activation plays a key role in the pathogenesis of pulmonary microvascular occlusion, which is a hallmark of severe coronavirus disease 2019 (COVID‐19). Consistent with EC activation, increased plasma von Willebrand factor antigen (VWF:Ag) levels have been reported in COVID‐19. Importantly however, studies in other microangiopathies have shown that plasma VWF propeptide (VWFpp) is a more sensitive and specific measure of acute EC activation. In the present study, we further investigated the nature of EC activation in severe COVID‐19. Markedly increased plasma VWF:Ag [median (interquatile range, IQR) 608·8 (531–830)iu/dl] and pro‐coagulant factor VIII (FVIII) levels [median (IQR) 261·9 (170–315) iu/dl] were seen in patients with severe severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection. Sequential testing showed that these elevated VWF–FVIII complex levels remained high for up to 3 weeks. Similarly, plasma VWFpp levels were also markedly elevated [median (IQR) 324·6 (267–524) iu/dl]. Interestingly however, the VWFpp/VWF:Ag ratio was reduced, demonstrating that decreased VWF clearance contributes to the elevated plasma VWF:Ag levels in severe COVID‐19. Importantly, plasma VWFpp levels also correlated with clinical severity indices including the Sequential Organ Failure Assessment (SOFA) score, Sepsis‐Induced Coagulopathy (SIC) score and the ratio of arterial oxygen partial pressure to fractional inspired oxygen (P/F ratio). Collectively, these findings support the hypothesis that sustained fulminant EC activation is occurring in severe COVID‐19, and further suggest that VWFpp may have a role as a biomarker in this setting.